The physiology of sucrose storage in sugarcane - Komor, Ewald (Carbohydrate Reserves in Plants - Synthesis and Regulation, 2000)
This short review concentrates on the transport and metabolism of sucrose and hexoses in the storage parenchyma of the sugarcane stalk. Unloading of sucrose from the phloem in the stalk has to proceed symplastically, because barriers around the bundle sheath of ripening stalks prevent apoplastic solute flow. Consequently, unloaded sucrose first appears in the cytosol of storage parenchyma. Sucrose then is subject to several cyclic processes in parallel: a metabolic cycle of sucrose hydrolysis and synthesis, a cycle of sucrose efflux and hexose uptake through plasmalemma-located transport systems, and a cycle of sucrose and hexose transfer into and out of the vacuole. The rate of these cyclic processes changes during the ripening of the internodes. In stalk parenchyma, where the transport rate through the tonoplast seems relatively low, intravacuolar acid invertase exerts the major control over the sucrose content of the cell. In case of rapid sucrose transfer over the tonoplast, as it happens in suspension cells, that control is lifted.